Synthesis of Calcium Glyceroxide Catalyst from Pensi Shells for CPO-Based Biodiesel Production - Addin Akbar; Dedy Rahmad; Eko Supriadi; Dwi Kemala Putri (Jurnal Kimia Sains dan Aplikasi, 2025)
The synthesis of a calcium glyceroxide catalyst derived from pensi shells for biodiesel production using crude palm oil (CPO) has been successfully conducted. The catalyst was prepared via the wet impregnation method by reacting CaO with glycerol in methanol as a solvent for 5 hours at 65°C, with catalyst-to-glycerol ratios of 1:1, 1:1.5, and 1:2. The glycerol used was obtained from crude glycerol, a by-product of biodiesel transesterification. CaO was derived from the calcination of pensi shells at 1000°C. The synthesized catalyst was tested for activity in biodiesel production from CPO. The test parameters included catalyst concentrations of 1.5%, 2%, and 2.5%, reaction times of 2 hours and 4 hours, and oil-to-methanol molar ratios of 1:5. The biodiesel yield for a 2-hour reaction time at catalyst concentrations of 1.5%, 2%, and 2.5% was 56.32%, 54.80%, and 50.19%, respectively. For a 4-hour reaction time at the same concentrations, the biodiesel yields were 40.28%, 60.73%, and 65.98%, respectively. Catalyst characterization was performed using XRD, XRF, SEM, and FTIR to support the activity test data. SEM analysis visually confirmed the bonding between CaO and glycerol. XRD results revealed the highest peaks at 2θ angles of 37.621° for CaO and 34.101° for Ca(OH)2, indicating a bond formation between CaO and glycerol. XRF analysis determined a CaO concentration of 96.21%. FTIR analysis identified the presence of glycerol through dominant -OH and C-O groups. The quality of the resulting biodiesel was tested against SNI (Indonesian National Standard) parameters. The analysis showed the highest methyl ester content (95.6%) at a reaction time of 4 hours. The highest oxidation stability (10.77 hours) was observed at a reaction time of 2 hours. Additional results included an acid number of 0.1%, total glycerol content of 0.279%-b, free glycerol content of 0.018%-b, and viscosity at 40°C of 3.559 mm2/s. The quality test results demonstrated that several parameters met SNI biodiesel standards.